Glass fiber reinforced PA12+PA6 composite material and preparation method thereof
通过在复合材料中使用改性玻璃纤维和三种偶联剂的复配,提升了PA6/PA12复合材料的低温冲击性能和抗水解能力,解决了低温冲击和耐磨性不足的问题,降低了 Water absorption rate broadens application scenarios.
Patent Information
- Application Number
- CN202411228697.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-31
AI Technical Summary
The existing composite materials lack performance in low temperature impact and wear resistance, and the glass fiber content is low and the surface modification treatment has not been performed, resulting in high water absorption and affecting the application of the material.
30-40% PA6 resin, 5-12% PA12 resin, 40-50% modified glass fiber, 0.4-2.5% compound coupling agent, 2-5% toughener, 0.4-0.8% The antioxidant and 0.2-0.6% lubricant are improved by the surface treatment of modified glass fibers and the combination of three coupling agents, and the mechanical properties and interface binding force of the material are reduced.
It significantly improves the low-temperature impact performance, hydrolysis resistance and high-temperature yellowing resistance of composite materials, reduces water absorption and broadens application scenarios.
Smart Images

Figure CN119220089A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a glass fiber reinforced PA12+PA6 composite material and a preparation method thereof. Background Art
[0002] PA6 is a synthetic fiber made from caprolactam monomers through polymerization. PA6 has excellent physical and chemical properties, and has the characteristics of high strength, high toughness, wear resistance, corrosion resistance, and high temperature resistance. It is widely used in textiles, industry, automobiles, electronics and other fields. The important direction of PA6 modification is glass fiber reinforcement, which can improve the comprehensive performance of nylon on the one hand and reduce costs on the other hand. Glass fiber reinforced PA6 modified materials are widely used in automotive parts. Since nylon 6 materials absorb water and have a high water absorption rate, the saturated water absorption rate is 10.7%. After nylon absorbs water, it will cause changes in the characteristics and dimensions of the parts. For example, if it absorbs water under the conditions of use, the changes may have a negative impact on many applications. Therefore, it is of great significance to reduce the water absorption of nylon materials.
[0003] The Chinese invention patent (CN110172243A) discloses a modified PA6 / PA12 alloy material with low water absorption and a preparation method. The composite material is modified by compounding the PA6 and PA12 alloys with a toughening system and lanthanum oxide, so that the composite material can achieve the performance of existing PA6 products while greatly reducing the water absorption of the material.
[0004] However, the patent does not mention the low-temperature impact and wear resistance of the material, nor does it explain the principle of reducing water absorption. The glass fiber content is low, and the glass fiber has not been surface-modified. Summary of the invention
[0005] The purpose of the present invention is to provide a glass fiber reinforced PA12+PA6 composite material and a preparation method thereof, aiming to solve the problems in the prior art that the composite material has low low-temperature impact, wear resistance and glass fiber content, and the glass fiber has not been surface modified.
[0006] To achieve the above object, the present invention provides the following technical solution: a glass fiber reinforced PA12+PA6 composite material, comprising the following components:
[0007] 30-40% by weight of PA6 resin;
[0008] 5-12% by weight of PA12 resin;
[0009] 40-50% by weight of modified glass fiber;
[0010] 0.4-2.5% by weight of a complex coupling agent;
[0011] The weight percentage is 2-5% toughening agent;
[0012] 0.4-0.8% antioxidant by weight;
[0013] The weight percentage is 0.2-0.6% lubricant.
[0014] In order to facilitate the preparation of PA6 resin by the glass fiber reinforced PA12+PA6 composite material, as a preferred embodiment of the present invention, the PA6 resin is a translucent or opaque milky white PA6 resin particle with a viscosity between 2.6-3.0.
[0015] In order to make the glass fiber reinforced PA12+PA6 composite material easy to prepare PA12 resin, as a preferred embodiment of the present invention, the PA12 resin is a semi-crystalline polyamide resin with a crystallinity between 45% and 65%.
[0016] In order to make the glass fiber reinforced PA12+PA6 composite material easy to prepare modified glass fiber, as a preferred embodiment of the present invention, the modified glass fiber is a homemade modified glass fiber, and the specific method is as follows: soaking the glass fiber in a dilute solution of a coupling agent, the solution is deionized water, the coupling agent concentration is 5-20%, the temperature is 60°C, soaking for 12h-18h, stirring the glass fiber slowly for 3-5min every 1h, and after soaking, putting the glass fiber into a blast drying oven at a temperature of 100-120°C for 8-12h, and drying is completed to obtain the modified glass fiber;
[0017] The complex coupling agent is a complex coupling agent of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane, and the weight ratio thereof is 1:1:(2-4).
[0018] In order to achieve the effect of adjusting the weight ratio of the complex linking agent to the glass fiber in the glass fiber reinforced PA12+PA6 composite material, as a preferred embodiment of the present invention, the weight percentage of the complex linking agent to the glass fiber is 3-5%.
[0019] In order to make the glass fiber reinforced PA12+PA6 composite material easy to select modified glass fiber, as a preferred embodiment of the present invention, the modified glass fiber is Jushi E8 glass fiber strand with a fiber diameter of 8-13 μm.
[0020] In order to facilitate the preparation of toughening agents for the glass fiber reinforced PA12+PA6 composite material, as a preferred embodiment of the present invention, the toughening agent is a maleic anhydride grafted ethylene propylene diene rubber with a grafting rate of 0.6-1.8%.
[0021] In order to make the glass fiber reinforced PA12+PA6 composite material easy to prepare antioxidants, as a preferred embodiment of the present invention, the antioxidant is a compound of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and bis(2,4-dicumylphenyl)pentaerythritol diphosphite, with a weight ratio of 1:3.
[0022] In order to facilitate the preparation of lubricants for the glass fiber reinforced PA12+PA6 composite material, as a preferred embodiment of the present invention, the lubricant is pentaerythritol stearate.
[0023] The preparation method of the glass fiber reinforced PA12+PA6 composite material, as a preferred method of the present invention, comprises the following steps:
[0024] S1: Place PA6 and PA12 resins in a forced air drying oven and dry them for 4-5 hours at a drying temperature of 80-100°C;
[0025] S2: Put PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mix for 1-3 minutes at a speed of 400-550 rpm to prepare a mixture 1;
[0026] S3: Mixture 1 is added by main feeding, glass fiber is added by side feeding, and the above raw materials are extruded and granulated by twin screws to obtain glass fiber reinforced PA6 / PA12 composite material. The extruder temperature is 180℃-250℃, the screw diameter is 35-75mm, the screw speed is 300-500rpm, and the screw aspect ratio is (40-44):1.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The glass fiber reinforced PA12+PA6 composite material and its preparation method use PA6 and PA12 resin to compound and add modified glass fiber to greatly reduce water absorption and improve the tensile, bending and impact properties of the composite material, especially the low-temperature impact performance; the glass fiber prepared by compounding three coupling agents can greatly improve the mechanical properties of the PA6 / PA12 / glass fiber ternary composite material, and the proportions of the three coupling agents are limited. The three interact with each other to improve the interfacial bonding force between the glass fiber and the composite nylon substrate, while isolating the contact between nylon 6 and water molecules, greatly reducing the water absorption rate; the use of maleic anhydride grafted EPDM rubber toughening agent can reduce the low-temperature impact strength of the composite material and broaden the application scenarios of the composite material; the use of bis(2,4-dicumylphenyl)pentaerythritol diphosphite can improve the high-temperature yellowing resistance of the composite material.
[0029] 2. The glass fiber reinforced PA12+PA6 composite material and its preparation method are compounded with three coupling agents and limited in comparative proportion, the purpose is to improve the interfacial bonding force between glass fiber and nylon substrate, soak the glass fiber, and the homemade glass fiber has a better surface effect, improves the interfacial bonding of the composite material, reduces water absorption, and improves the hydrolysis resistance; E8 glass is added, and its excellent mechanical properties make the comprehensive performance of the composite material even better. Adding toughening agent can further improve the low-temperature impact performance of the composite material; compounded antioxidants are used, among which bis(2,4-dicumylphenyl) pentaerythritol diphosphite is used as an antioxidant that is resistant to high temperature yellowing, making the application scenarios of the material more extensive. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 This is a schematic diagram of the structure of the glass fiber reinforced PA6 / PA12 composite material of the present invention;
[0032] Figure 2 It is a schematic diagram of the performance test result structure in the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] See also Figure 1-2 , the present invention provides the following technical solution: a glass fiber reinforced PA12+PA6 composite material, comprising the following components: 30-40% by weight of PA6 resin;
[0036] 5-12% by weight of PA12 resin;
[0037] 40-50% by weight of modified glass fiber;
[0038] 0.4-2.5% by weight of a complex coupling agent;
[0039] The weight percentage is 2-5% toughening agent;
[0040] 0.4-0.8% antioxidant by weight;
[0041] The weight percentage is 0.2-0.6% lubricant.
[0042] In this embodiment, the viscosity of PA6 is 2.6, the crystallinity of PA12 is 55%, the coupling agent concentration is 10%, the immersion time is 16 hours, and the coupling agent ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane is 1:1:2.
[0043] Preparation method:
[0044] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 4 hours at a drying temperature of 100°C.
[0045] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 2 minutes at a speed of 500 rpm to prepare a mixture 1;
[0046] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 65mm, the screw speed is 450rpm, and the screw length-diameter ratio is 40:1.
[0047] Example 2
[0048] The present invention provides the following technical solution: A glass fiber reinforced PA12+PA6 composite material, the raw material formula and composition of which are shown in Figure 1 .
[0049] In this embodiment: the viscosity of PA6 is 2.8, the crystallinity of PA12 is 65%, the coupling agent concentration is 15%, the immersion time is 15h, and the coupling agent ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane is 1:1:3.
[0050] Preparation method:
[0051] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 5 hours at a drying temperature of 80°C;
[0052] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 3 minutes at a speed of 400 rpm to prepare a mixture 1;
[0053] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 55mm, the screw speed is 500rpm, and the screw length-diameter ratio is 40:1.
[0054] Example 3
[0055] The present invention provides the following technical solution: A glass fiber reinforced PA12+PA6 composite material, the raw material formula and composition of which are shown in Figure 1 .
[0056] In this embodiment: the viscosity of PA6 is 2.8, the crystallinity of PA12 is 65%, the coupling agent concentration is 20%, the immersion time is 14h, and the coupling agent ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane is 1:1:4.
[0057] Preparation method:
[0058] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 4 hours at a drying temperature of 100°C.
[0059] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 2 minutes at a speed of 500 rpm to prepare a mixture 1;
[0060] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 65mm, the screw speed is 500rpm, and the screw length-diameter ratio is 40:1.
[0061] Example 4
[0062] The present invention provides the following technical solution: A glass fiber reinforced PA12+PA6 composite material, the raw material formula and composition of which are shown in Figure 1 .
[0063] In this embodiment: the viscosity of PA6 is 3.0, the crystallinity of PA12 is 45%, the coupling agent concentration is 15%, the immersion time is 12 hours, and the coupling agent ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane is 1:1:4.
[0064] Preparation method:
[0065] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 5 hours at a drying temperature of 80°C.
[0066] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 1 min at a speed of 550 rpm to prepare a mixture 1;
[0067] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 75mm, the screw speed is 400rpm, and the screw length-diameter ratio is 40:1.
[0068] Example 5
[0069] The present invention provides the following technical solution: A glass fiber reinforced PA12+PA6 composite material, the raw material formula and composition of which are shown in Figure 1 .
[0070] In this embodiment: the viscosity of PA6 is 2.8, the crystallinity of PA12 is 55%, the coupling agent concentration is 15%, the immersion time is 16 hours, and the coupling agent ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane is 1:1:2.
[0071] Preparation method:
[0072] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 5 hours at a drying temperature of 80°C.
[0073] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 2 minutes at a speed of 500 rpm to prepare a mixture 1;
[0074] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 35mm, the screw speed is 300rpm, and the screw length-diameter ratio is 44:1.
[0075] Example 6
[0076] The present invention provides the following technical solution: A glass fiber reinforced PA12+PA6 composite material, the raw material formula and composition of which are shown in Figure 1 .
[0077] In this embodiment: the viscosity of PA6 is 3.0, the crystallinity of PA12 is 55%, the coupling agent concentration is 5%, the immersion time is 18h, and the coupling agent ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane is 1:1:3.
[0078] Preparation method:
[0079] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 4 hours at a drying temperature of 100°C.
[0080] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 3 minutes at a speed of 400 rpm to prepare a mixture 1;
[0081] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 50mm, the screw speed is 500rpm, and the screw length-diameter ratio is 40:1.
[0082] Comparative Example 1
[0083] The present invention provides the following technical solution: A glass fiber reinforced PA12+PA6 composite material, the raw material formula and composition of which are shown in Figure 1 .
[0084] In this embodiment: the viscosity of PA6 is 2.8, the crystallinity of PA12 is 65%, and the glass fiber is unmodified E8 glass fiber.
[0085] Preparation method:
[0086] S1. Place PA6 and PA12 resins in a forced air drying oven and dry them for 4 hours at a drying temperature of 100°C.
[0087] S2, putting PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mixing for 2 minutes at a speed of 500 rpm to prepare a mixture 1;
[0088] S3, adding the mixed material 1 by the main feeding method, adding the glass fiber by the side feeding method, and obtaining the glass fiber reinforced PA6 / PA12 composite material after the above raw materials are twin-screw extruded and granulated. The extruder temperature is 180℃-250℃, the screw diameter is 65mm, the screw speed is 500rpm, and the screw length-diameter ratio is 40:1.
[0089] Comparative Example 2
[0090] Referring to Example 3, only 3-(2,3-epoxypropoxy)propyltrimethoxysilane was used as the coupling agent, and the rest remained unchanged.
[0091] Comparative Example 3
[0092] Referring to Example 3, only γ-(methacryloyloxy)propyltrimethoxysilane was used as the coupling agent, and the rest remained unchanged.
[0093] Comparative Example 4
[0094] Referring to Example 3, only dodecyltrimethoxysilane was used as the coupling agent, and the rest remained unchanged.
[0095] Comparative Example 5
[0096] Referring to Example 3, the ratio of the compound coupling agent is 1:1:1, and the rest remains unchanged.
[0097] Comparative Example 6
[0098] Referring to Example 3, the ratio of the compound coupling agent is 1:1:6, and the rest remains unchanged.
[0099] Comparative Example 7
[0100] Referring to Example 3, the toughening agent is maleic anhydride grafted SEBS, and the rest remains unchanged.
[0101] The glass fiber reinforced PA6 / PA12 composite materials prepared in Examples 1-6 and Comparative Examples 1-7 were tested according to the following performance standards: 1. Tensile test: measured according to GB / T 1040.1; 2. Bending test: measured according to GB / T 9341; 3. Simple beam notched impact strength: measured according to GB / T 1043.1. 4. Equilibrium water absorption: measured according to GB / T 1034-2008, at 23°C and 50%RH, the water content of the material when it absorbs water to reach an equilibrium state.
[0102] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0103] Table 1 Glass fiber reinforced PA6 / PA12 composites
[0104]
[0105] Table 2 Performance test results of Examples 1-6 and Comparative Examples 1-7
[0106]
Claims
1. A glass fiber reinforced PA12+PA6 composite material, characterized in that: The invention comprises the following components: 30-40% by weight of PA6 resin; 5-12% by weight of PA12 resin; 40-50% by weight of modified glass fiber; 0.4-2.5% by weight of a complex coupling agent; The weight percentage is 2-5% toughening agent; 0.4-0.8% antioxidant by weight; The weight percentage is 0.2-0.6% lubricant.
2. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The PA6 resin is a translucent or opaque milky white PA6 resin particle with a viscosity between 2.6 and 3.
0.
3. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The PA12 resin is a semi-crystalline polyamide resin with a crystallinity between 45% and 65%.
4. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The modified glass fiber is a homemade modified glass fiber, and the specific method is as follows: soaking the glass fiber in a dilute solution of a complex coupling agent, the solution is deionized water, the coupling agent concentration is 5-20%, the temperature is 60°C, soaking for 12h-18h, slowly stirring the glass fiber for 3-5min every 1h, and after soaking, putting the glass fiber into a blast drying oven at a temperature of 100-120°C for 8-12h, and drying to obtain the modified glass fiber; The complex coupling agent is a complex coupling agent of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane, and the weight ratio thereof is 1:1:(2-4).
5. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The weight percentage of the composite coupling agent to the glass fiber is 3-5%.
6. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The modified glass fiber is made of Jushi E8 glass fiber raw yarn with a fiber diameter of 8-13 μm.
7. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The toughening agent is a maleic anhydride grafted EPDM rubber with a grafting rate of 0.6-1.8%.
8. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The antioxidant is a compound of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine and bis(2,4-dicumylphenyl) pentaerythritol diphosphite, with a weight ratio of 1:
3.
9. The glass fiber reinforced PA12+PA6 composite material according to claim 1, characterized in that: The lubricant is pentaerythritol stearate.
10. A method for preparing a glass fiber reinforced PA12+PA6 composite material according to claims 1-9, characterized in that: The following steps are involved: S1: Place PA6 and PA12 resins in a forced air drying oven and dry them for 4-5 hours at a drying temperature of 80-100°C; S2: Put PA6 resin, PA12 resin, toughening agent, antioxidant and lubricant into a high-speed mixer, mix for 1-3 minutes at a speed of 400-550 rpm to prepare a mixture 1; S3: Mixture 1 is added by main feeding, glass fiber is added by side feeding, and the above raw materials are extruded and granulated by twin screws to obtain glass fiber reinforced PA6 / PA12 composite material. The extruder temperature is 180℃-250℃, the screw diameter is 35-75mm, the screw speed is 300-500rpm, and the screw aspect ratio is (40-44):1.
